2011
DOI: 10.1021/es1037904
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution and Polycyclic Aromatic Hydrocarbons Emissions from Agricultural Crop Residue Burning

Abstract: Laboratory measurements were conducted to determine particle size distribution and polycyclic aromatic hydrocarbons (PAHs) emissions from the burning of rice, wheat, and corn straws, three major agricultural crop residues in China. Particle size distributions were determined by a wide-range particle spectrometer (WPS). PAHs in both the particulate and gaseous phases were simultaneously collected and analyzed by GC-MS. Particle number size distributions showed a prominent accumulation mode with peaks at 0.10, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
113
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(128 citation statements)
references
References 33 publications
9
113
1
Order By: Relevance
“…For example, particlebound PAHs freshly emitted from combustion of liquid fossil fuel are mainly distributed in the ultrafine fractions (Miguel et al, 1998;Shi et al, 2000;Phuleria et al, 2006), but unimodal size distributions of PAHs peaking at large particle sizes have been observed from rice straw and corn straw burning, which often proceeds at lower temperatures than combustion of liquid fossil fuel (Hays et al, 2005;Li et al, 2007;Zhang et al, 2011). The size distributions of PAHs in winter in Guangzhou (Figs.…”
Section: Particle Size Distribution Of Pahsmentioning
confidence: 99%
“…For example, particlebound PAHs freshly emitted from combustion of liquid fossil fuel are mainly distributed in the ultrafine fractions (Miguel et al, 1998;Shi et al, 2000;Phuleria et al, 2006), but unimodal size distributions of PAHs peaking at large particle sizes have been observed from rice straw and corn straw burning, which often proceeds at lower temperatures than combustion of liquid fossil fuel (Hays et al, 2005;Li et al, 2007;Zhang et al, 2011). The size distributions of PAHs in winter in Guangzhou (Figs.…”
Section: Particle Size Distribution Of Pahsmentioning
confidence: 99%
“…The aerosols affect regional, and possibly global, radiation budgets by their light-scattering effects and influence on cloud microphysical processes. Various studies have been published dealing with the amount of biomass burned from various sources such as deforestation, shifting cultivation, savanna fires, fuel wood and the burning of agricultural residues mainly in tropical regions (Wang et al, 2007, Cao et al, 2008, Zhang et al, 2011. On a global basis, forest burning is the major source of the fire emissions due to its high carbon density and burning of agricultural waste is the second major source, representing nearly 2020 Tg (approx 25% of total biomass burned) (Crutzen and Andreae, 1990;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers opt for burning because it is a quick and easy way to manage the large quantities of crop residues and prepare the field for the next crop well in time. Agricultural residues burning may emit significant quantity of air pollutants like CO 2 , N 2 O, CH 4 , emission of air pollutants such as CO, NH 3 , NO x , SO 2 , NMHC, volatile organic compounds (VOCs) and semi-volatile organic compounds (SVOCs) and particulate matter like elemental carbon at a rate far different from that observed in savanna/forest fire due to different chemical composition of the crop residues and burning conditions (Zhang et al, 2011, Mittal et al, 2009. Several researchers have estimated the emission of different species from crop residue burning using IPCC factors, but they have covered only few gaseous pollutants (N 2 O, CH 4 , NO x , and SO 2 ) (Venkataraman et al, 2006;Sahai et al, 2007); or from a specific area and crop (Badrinath et al, 2006;Sahai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that more than 550 million tons of biomass was burned in China in year of 2005 (National Bureau of Statistics, 2006). Biomass burning is known as a significant source of gaseous and particulate pollutants to the atmosphere, which causes serious local and regional air pollution (Levine et al, 1995;Andreae et al, 2005;Koppmann et al, 2005;Bo et al, 2008;Li et al, 2008;Wei et al, 2008;Zhang et al, 2011). Moreover, some of the emissions with hazardous pollutants have adverse impacts on human health (Johnson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%